Konsep Liquid Life Menurut Zygmunt Bauman - Kurniawan, Ryan (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2024)
Bauman, who is famous for his views on post-modernity which he called liquid modernity, introduced in one of his works Liquid Life that the life lived by people living in liquid modernity is liquid life. He described liquid life as dangerous. It is said to be dangerous because life is full of uncertainty and is always in continuous change and occurs in a fast time. This then creates great fear for individu because he is haunted by the inability to keep up with changes and lag behind. By discussing this concept, the author seeks to show what liquid life is and how it affects human life. As a totality, life certainly includes all aspects possessed by humans. Then from the whole description, the author invites the reader to see, is liquid life solely marked by negative things? Or is there a blessing in disguise in it.